Health impact assessment (HIA): lessons from Thailand - Pornchai Sithisarankul (College of Community Physicians of Sri Lanka, 2014)
DOI: http://dx.doi.org/10.4038/jccpsl.v19i1.7625 Journal of the College of Community Physicians of Sri Lanka Vol.19(1) December 2013 42-44